Application Of Dance Movement In Improving Symbolic Thinking Skills In Children - Titi Rachmi; Nurul Fitria Kumala Dewi; Enike Putri (UIN Sultan Maulana Hasanudin Banten, 2024)
The aim of the research is to determine the symbolic thiking skills of children aged 5-6 years through dance movements. The method used was classroom action research conducted in three cycles. Data collection methode used in this research were observation, documentation, interviews and field notes. The subjects of this research were group B children who experienced problems in symbolic thinking such as recognizing number and letter symbols, matching number names with number pictures, children had difficulty distinguishing the shapes of numbers and letters which were almost the same. Based on the results of the research in cycle 1, it showed that there was an increase in children’s symbolic thinking skills between before and after giving action to children aged 5-6 years at PAUD SPS Cempaka. This is evidenced by an increase in the first cycle of 8,7%, from the initial conditions of 34,4% to 43.1%, the second cycle experienced an increase of 21,2%, from the initial conditions of 34,4% to 55,6% in cycle III there was an increase of 42,3% in the initial conditions of 34,4% to 76,7%. This can be concluded that the application of dance moves can improve children’s symbolic thinking skills at the age of 5-6 years.